Gladiolous: An exploration of the Gladiolous plant and its taxonomy (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Gladiolous is sometime called the ‘sword lily’, but usually by its generic name (plural gladioli). Botanical name – galdiaclus –spp, Family-irdaceae.